Sexual Assault: Indigenous Women's Experiences of Not Being Believed by the Police. (April 2022) - Murphy-Oikonen, Jodie; Chambers, Lori; McQueen, Karen; Hiebert, Alexa; Miller, Ainsley
Rates of sexual victimization among Indigenous women are 3 times higher when compared with non-Indigenous women. The purpose of this secondary data analysis was to explore the experiences and recommendations of Indigenous women who reported sexual assault to the police and were not believed. This qualitative study of the experiences of 11 Indigenous women reflects four themes. The women experienced (a) victimization across the lifespan, (b) violent sexual assault, (c) dismissal by police, and (d) survival and resilience. These women were determined to voice their experience and make recommendations for change in the way police respond to sexual assault.